2017
DOI: 10.1080/02640414.2017.1410875
|View full text |Cite
|
Sign up to set email alerts
|

Sodium bicarbonate improves 4 km time trial cycling performance when individualised to time to peak blood bicarbonate in trained male cyclists

Abstract: The aim of this study was to investigate the effects of sodium bicarbonate (NaHCO) on 4 km cycling time trial (TT) performance when individualised to a predetermined time to peak blood bicarbonate (HCO). Eleven male trained cyclists volunteered for this study (height 1.82 ± 0.80 m, body mass (BM) 86.4 ± 12.9 kg, age 32 ± 9 years, peak power output (PPO) 382 ± 22 W). Two trials were initially conducted to identify time to peak HCO following both 0.2 gkg BM (SBC2) and 0.3 gkg BM (SBC3) NaHCO. Thereafter, on thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
87
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(100 citation statements)
references
References 33 publications
10
87
1
2
Order By: Relevance
“…The protocols for the TT, including the self-selected warm-up, were identical to those detailed in the previous research (Gough et al 2017c), whereby only cadence and gear was displayed to the participant. Each TT series was preceded by supplementation of one of the SBC2, SBC3, or a taste-matched placebo (0.07 g kg −1 BM sodium chloride; PLA) administered in a block-randomized order.…”
Section: Methodsmentioning
confidence: 99%
“…The protocols for the TT, including the self-selected warm-up, were identical to those detailed in the previous research (Gough et al 2017c), whereby only cadence and gear was displayed to the participant. Each TT series was preceded by supplementation of one of the SBC2, SBC3, or a taste-matched placebo (0.07 g kg −1 BM sodium chloride; PLA) administered in a block-randomized order.…”
Section: Methodsmentioning
confidence: 99%
“…This could be related to differences in time to peak alkalosis. Therefore, the timing of NaHCO 3 administration prior to exercise can be individualized to ensure that blood [HCO 3 -] for each individual peaks at exercise onset [12]. Unfortunately, predetermination of the time to peak blood [HCO 3 -] is rather time consuming, as it requires multiple visits to the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies also found a performance benefit of NaHCO3 ingestion during 4000-m cycling time trials performed by trained male cyclists. 16,17 The cause of the difference in effect might be due to the individual variation in time to peak alkalosis. 16 Gough et al 16,17 used an individualized supplementation strategy, in which NaHCO3 supplements are ingested at a time point which results in peak pH and/or HCO3concentrations at the start of the time trial for each individual.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The cause of the difference in effect might be due to the individual variation in time to peak alkalosis. 16 Gough et al 16,17 used an individualized supplementation strategy, in which NaHCO3 supplements are ingested at a time point which results in peak pH and/or HCO3concentrations at the start of the time trial for each individual. In the current study an individualized supplementation strategy was not used, which possibly limited the ergogenic effect on cycling performance in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation